2024
DOI: 10.1039/d3cp04224c
|View full text |Cite
|
Sign up to set email alerts
|

Constructing perfect cubic Ag–Cu alloyed nanoclusters through selective elimination of phosphine ligands

Li Tang,
Qikai Han,
Bin Wang
et al.

Abstract: The aspiration of chemists has always been to design and achieve control over nanoparticle morphology at the atomic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In the case of Cu alloying, the Cu atoms tend to position themselves in the shell layer of the core–shell NCs. 30–35 Zhu et al reported bimetallic NCs, Au 36− x Cu x ( m -MBT) 24 ( x = 1–3), 30 Au 38− x Cu x (2,4-DMBT) 24 ( x = 0–6, DMBT = 2,4-dimethylbenzenethiolate), 31 and [Ag 62− x Cu x S 12 (SBu t ) 32 ] 4+ ( x = 10–21). 32 Liu et al reported bimetallic Cu x Ag 20− x {S 2 P(OR) 2 } 12 ( x = 3, 4; R = i Pr, 19 n Pr 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Cu alloying, the Cu atoms tend to position themselves in the shell layer of the core–shell NCs. 30–35 Zhu et al reported bimetallic NCs, Au 36− x Cu x ( m -MBT) 24 ( x = 1–3), 30 Au 38− x Cu x (2,4-DMBT) 24 ( x = 0–6, DMBT = 2,4-dimethylbenzenethiolate), 31 and [Ag 62− x Cu x S 12 (SBu t ) 32 ] 4+ ( x = 10–21). 32 Liu et al reported bimetallic Cu x Ag 20− x {S 2 P(OR) 2 } 12 ( x = 3, 4; R = i Pr, 19 n Pr 33 ).…”
Section: Introductionmentioning
confidence: 99%